ANALISIS PENGAWASAN PROGRAM PEMUDA SARJANA PENGGERAK PEMBANGUNAN PEDESAAN DI PROVINSI SULAWESI TENGAH (STUDI KASUS DI DESA AMPIBABO UTARA) - Riyatno, Riyatno (Katalogis, 2015)
This study aims at analyzing the Monitoring of Development Activator Youth Scholar Program in Central Sulawesi (A Case Study in the village of Ampibabo Utara). The number of informants in the study are 8 people, namely three people of the Technical Team PSP3, the head section of Youth Leadership, Secretary of the village and two people of PSP3 participants also a civilian. The technique used in determining the informant is purposive by choosing informants purposively. Data collection techniques in this research are observation, interviews and documentation. The result shows that Monitoring of Development Activator Youth Scholar Program in Central Sulawesi has already implemented but it has not been optimal. This is proved by the results of interviews viewed from the dimensions of direct inspection with indicators stating that monitoring implementation in the form of direct inspection is not carried out in accordance with the applicable rules, to be exact 2 twice in a month, but it is carried out in 3 to 4 months with an unspecified time which is resulting the inactivity of PSP3 participants in the placement location in implementing the programs and also the report in place has not been established by PSP3 in accordance with what is assigned because the PSP3 participants have not prepared the report of work they performed. As for the dimensions of indirect inspection, it has been executed properly, which it can be seen from the indicators of written and oral reports.